Full Spectrum Collection of Concentrated Solar Energy Using PV Coupled with Selective Filtration Utilizing Nanoparticles. Issue 43 (10th June 2016) - Otanicar, Todd; DeJarnette, Drew; Brekke, Nick; Tunkara, Ebrima; Roberts, Ken; Harikumar, Parameswar
ABSTRACT: Hybrid solar receivers utilizing both photovoltaic cells and thermal collectors are capable of collecting the entire solar spectrum for use in energy systems. Such systems provide efficient solar energy conversion using PV in addition to dispatchability through thermal storage by incorporating a thermal collector in conjunction with the PV. Proposed hybrid systems typically invoke spectrum splitting so to redirect photons optimized for PV electric conversion to a cell while non-PV efficient photons are directed to a thermal absorber. This work discusses a hybrid system with a selective solar filter using a suspended nanoparticle fluid to directly absorb non-PV photons. Non-absorbed photons pass through the filter and impact the PV. Choice of nanoparticles in the fluid allow absorption and transmission of specific wavelengths. Nanoparticles were chosen based on optimization simulations for a bandpass filter to a cSi solar cell. The synthesized fluid has been experimentally characterized to show the effects of high temperature on nanoparticle stability and optical properties. Thermodynamic modeling of the system suggests solar to electric efficiency of the total system is 23.2% if all thermal energy is converted to electricity through an organic Rankine cycle (ORC). However, high temperature generation could be used for industrial process heat at a specific temperature by changing parameters such as absorbed energy and flow rates. Furthermore, a prototype is being developed with 14x concentration to demonstrate the technology on-sun with initial testing targeted for the 2nd quarter of 2016. Overall, the hybrid nanoparticle filter concentrating solar collector can be modified to fit a variety of applications through easily changeable parameters in the system.